Invasion sports in physical education according to the BNCC: An integrative review - Carvalho, Adelson do Socorro Ferreira de; Sena, Elinaldo Viana; Junior , Jose Robertto Zaffalon; Oliveira, Jorge Farias de; Silva, Rosângela Lima da; Monte, Fernanda Silva do; Mendes, Francivaldo José da Conceição; Sousa, Smayk Barbosa; Cabreira, Alesandra Negrete; Cabreira, Juliane Umann; Melo, Gileno Edu Lameira de (Seven Editora, 2024)
This study arises from the need for a pedagogical approach that goes beyond the technical teaching of invasion sports, aligning with the principles of the National Common Curricular Base (BNCC) to promote the integral development of students. The objective of the study was to analyze the contribution of invasion sports in the integral formation of students according to the BNCC. The integrative literature review, carried out in the last 10 years in relevant scientific journals, resulted in the selection of 11 studies. These studies highlight the relevance of invasion sports not only for physical development, but also for socio-emotional skills, ethics, and respect for the rules recommended by the BNCC. The results indicate the importance of teachers recognizing and exploring the educational potential of these modalities, promoting enriching experiences. It is concluded that the analysis of the selected studies highlight that invasion sports provide opportunities for students to experience, enjoy and understand different body practices, giving relevance to this object of knowledge in School Physical Education. DOI:https://doi.org/10.56238/sevened2024.012-021